A Portrait Of Religious Moderation Amid Pluralism And Diversity To Build Interfaith Harmony In Balun Village, Lamongan Regency - Miftakhul Muthoharoh; Moh. Rofik Fitrotulloh; Ihya’ Ulumuddin (Green Publisher Indonesia, 2024)
In the midst of the rising issues of intolerance and radicalism occurring in various regions of Indonesia, Balun Village in Turi District, Lamongan Regency, stands out as one of the cities with a high tolerance index in East Java. The focus of this research is to examine the patterns of social interaction among different religious communities in building harmony and peaceful coexistence within the multicultural society of Balun Village, Lamongan Regency. It also aims to capture the portrait of religious moderation based on local wisdom in Balun Village to maintain interfaith harmony. The research uses qualitative fieldwork methods to clearly depict the social interactions between religious groups in fostering harmony at the research location. The approach used in this study is phenomenology to empirically understand how the residents of Balun Village, perceive, express, and practice religious moderation based on local wisdom to maintain interfaith harmony. Data for this study were collected using two techniques: interviews and observations. Data analysis is conducted using the analytical methods of Miles, Huberman, and Saldana, which include three steps: data condensation, data display, and conclusion drawing and verification. Social interactions between Muslims and non-Muslims in Balun Village are characterized by associative processes such as cooperation, accommodation, and acculturation. The empirical portrait of how the residents of Balun Village understand, express, and practice religious moderation based on local wisdom includes various activities such as wedding celebrations (kenduri), death rituals, communal work, arts performances, Nyadran rituals, Tunduan, and mutual cooperation in religious rituals and major religious holidays.